2018
DOI: 10.1002/jcp.27455
|View full text |Cite
|
Sign up to set email alerts
|

Glucose intolerance in monosodium glutamate obesity is linked to hyperglucagonemia and insulin resistance in α cells

Abstract: Obesity predisposes to glucose intolerance and type 2 diabetes (T2D). This disease is often characterized by insulin resistance, changes in insulin clearance, and β-cell dysfunction. However, studies indicate that, for T2D development, disruptions in glucagon physiology also occur. Herein, we investigated the involvement of glucagon in impaired glycemia control in monosodium glutamate (MSG)-obese mice. Male Swiss mice were subcutaneously injected daily, during the first 5 days after birth, with MSG (4 mg/g bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Some researchers also proposed that a significant increase in blood glucose after MSG administration was probably because of its conversion glutamic acid moiety of MSG to oxalacetate by D-amino acid oxidase thereby producing glucogenic precursor [6]. Also, in support of the findings of this study, Araujo et al, [34] suggested that the hyperglycaemic effect of MSG could arise as a result of poor ability to oxidize glutamic acid in the pancreatic cells and that MSG acts via phosphoenolpyruvate carboxykinase in decreasing blood glucose. The study of Dayer and Dayer,[35] validates the findings of this present study, showing no significant alterations in plasma insulin concentration in short term administration of low and medium doses of MSG which was attributed to the low stimulation of glutamate receptors in β pancreatic cell [31].…”
Section: Discussionsupporting
confidence: 82%
“…Some researchers also proposed that a significant increase in blood glucose after MSG administration was probably because of its conversion glutamic acid moiety of MSG to oxalacetate by D-amino acid oxidase thereby producing glucogenic precursor [6]. Also, in support of the findings of this study, Araujo et al, [34] suggested that the hyperglycaemic effect of MSG could arise as a result of poor ability to oxidize glutamic acid in the pancreatic cells and that MSG acts via phosphoenolpyruvate carboxykinase in decreasing blood glucose. The study of Dayer and Dayer,[35] validates the findings of this present study, showing no significant alterations in plasma insulin concentration in short term administration of low and medium doses of MSG which was attributed to the low stimulation of glutamate receptors in β pancreatic cell [31].…”
Section: Discussionsupporting
confidence: 82%
“…As previously demonstrated (Araujo et al 2019, Bonfleur et al 2015, Macho et al 2000, Nardelli et al 2011, Oida et al 1984, from 30 to 120 days of age, MSG mice displayed similar BW (Fig. 1b and 1c), food ( Fig.…”
Section: Obesity Evaluationsupporting
confidence: 81%
“…Food consumption was measured once a week and water intake was measured every two days; results are expressed as the food or water ingestion per day. Feed efficiency was obtained by the ratio from the total BW gained, divided by the total food consumption before or during the treatment period (Araujo et al 2019).…”
Section: Food and Water Intake Obesity And Biochemical Parametersmentioning
confidence: 99%
“…Thus, circulating glutamate is positively related to visceral obesity and posterior development of MetS [154]. In a pre-clinical study, IR was correlated with glutamate in mice treated with monosodium glutamate to develop obesity [49]. Moreover, in obese morbid patients, those with pre-diabetes were found to have higher serum glutamate levels compared to non-diabetic controls.…”
Section: Glutamate Family: Glutamine and Glutamatementioning
confidence: 97%